Doppler Evaluation of Left to Right Shunt (Qp/Qs) in Patients with Isolated Ventricular Septal Defect (Vsd) - Mahmood, M; Haque, SS; Siddique, MA; Ahmed, CM; Hossain, Z (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 181-186The abstract of this article is available on the PubMed website